2019
DOI: 10.3390/soilsystems3010020
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Sorption Speciation and Precipitation Mechanisms on Amorphous Aluminum Hydroxide

Abstract: Aluminum (Al) oxides are important adsorbents for phosphate in soils and sediments, and significantly limit Phosphate (P) mobility and bioavailability, but the speciation of surface-adsorbed phosphate on Al oxides remains poorly understood. Here, phosphate sorption speciation on amorphous Al hydroxide (AAH) was determined under pH 3–8 and P concentration of 0.03 mM–15 mM using various spectroscopic approaches, and phosphate precipitation mechanisms were discussed as well. AAH exhibits an extremely high phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 56 publications
(90 reference statements)
0
31
0
Order By: Relevance
“…(2001) reported that oxalate‐extractable Al and Fe were responsible for P adsorption in 35‐ to 40‐yr‐old agricultural soils. Also, Podzols, which are rich in amorphous Al hydroxide, are accountable for fixing P via surface complexation and precipitation reaction (Wang et al., 2019). We may conclude that high P adsorption in the tested forested and managed Podzol horizons is mainly influenced by the combined effect of SOM, Al, and Fe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2001) reported that oxalate‐extractable Al and Fe were responsible for P adsorption in 35‐ to 40‐yr‐old agricultural soils. Also, Podzols, which are rich in amorphous Al hydroxide, are accountable for fixing P via surface complexation and precipitation reaction (Wang et al., 2019). We may conclude that high P adsorption in the tested forested and managed Podzol horizons is mainly influenced by the combined effect of SOM, Al, and Fe.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of high SOM in SJRDC forested B horizon and higher Al in SJRDC forested BC horizon might explain the apparently similar q max values (Table 3). The amorphous Al minerals in Podzols form a firm surface complexation or precipitation with P added as fertilizer (Wang et al., 2019; Weihrauch & Opp, 2018). Also, organically bound Al has been reported to be responsible for 60% of P retention, of which about 70% is nonlabile P (Villapando & Graetz, 2001) but with the potential of being released in low‐P soils (Zhou et al., 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Guo et al assigned the two dominating resonances at δ iso ( 31 P) = -14.5 and -7.5 ppm in the 31 P MAS NMR spectrum to phosphate associated with the LDH. 49 However, δ iso ( 31 P) = -14.5 ppm are in the same range as aluminum phosphate synthesized under acid condition 36,39,60 and δ iso ( 31 P) = -7.5 ppm match newberyite. 27,61,69 Both minerals are also clearly identified by PXRD.…”
Section: Comparison With Earlier Combined Pxrd and 31 P Ssnmr Studiesmentioning
confidence: 70%
“…2 ). These organic subfractions of P therefore appear to be sorbed onto and incorporated into complexes of organic matter and amorphous sesquioxides, especially Al o (Wang et al 2019 ). This P is more available than that associated with crystallising sesquioxides, but its recycling depends on the dynamics of the complexes, and the rate at which the organic components are decomposed (Barthes et al 2008 ; Hernandez-Soriano 2012 ).…”
Section: Discussionmentioning
confidence: 99%